Hydrogel-embedded nanocrystalline hydroxyapatite granules (elastic blocks) based on a cross-linked polyvinylpyrrolidone as bone grafting substitute in a rat tibia model - Dau M (Dove Medical Press, 2017)
Michael Dau,1 Cornelia Ganz,2 Franziska Zaage,2 Bernhard Frerich,1 Thomas Gerber2 1Department of Oral, Maxillofacial and Plastic Surgery, University Medical Center Rostock, Rostock, Germany; 2Institute of Physics, Rostock University, Rostock, Germany Purpose: The aim of this study was to examine the in vivo characteristics and levels of integration and degradation of a ready-to-use bone grafting block with elastic properties (elastic block) for the use in surgery. Materials and methods: Thirty-six male Wistar rats underwent surgical creation of a well-defined bone defect in the tibia. All created defects – one per animal – were filled with an unsintered nanocrystalline hydroxyapatite embedded either with a non-cross-linked hydrogel carrier (CONT, n=18) or a cross-linked hydrogel carrier (elastic block [EB], n=18) based on polyvinylpyrrolidone (PVP) and silica sol, respectively. The animals were killed after 12 (n=12), 21 (n=12) and 63 days (n=12). The bone formation and defect healing were quantified by histomorphometric measurements made in paraffin sections. Additionally, immunohistochemical (tartrate-resistant acid phosphatase [TRAP] and alkaline phosphatase [aP]), antibody-based examinations (CD68) and energy-dispersive x-ray scattering measurements of silica atom concentration were carried out. Results: A larger remaining bone defect area overall was observed in EB after 12 days and 21 days. After 63 days, similar areas of remaining bone defects were found. The amount of the remaining carrier material in EB overall was higher at all times. In CONT no residual carrier material was found at 12 days and later. CD68 analyses showed significantly lower level of CD68-positive marked cells after 21 days in CONT, and nonsignificant differences at 12 and 63 days, respectively. Additionally, a significantly higher level of aP-positive marked cells was observed in CONT after 12 days. Later on, the levels of aP-positive marked cells were slightly higher in EB (21 and 63 days). Furthermore, no significant differences regarding the level of TRAP-positive marked cells in each group were observed. Conclusion: The bone substitute (EB) with the cross-linked PVP-based hydrogel carrier leads at the beginning to a higher amount of remaining carrier material and remaining bone substitute. This delayed degradation is supposed to be the reason for the observed lower level of bone remodeling and is caused by the irradiation changes (cross links) in the structure in PVP.Keywords: bone substitute, cross-linked, nanocrystalline hydroxyapatite, rat animal model, polyvinylpyrrolidone, irradiation, silica, osseointegration